Perancangan Buku Referensi Karakteristik Tata Rias Tari Surabaya Dengan Teknik Fotografi Sebagai Sarana Informasi Masyarakat Surabaya - Islamiyah, Ainun; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Abstract: The Great Indonesian Dictionary (KBBI) defines a reference book as a guidance, hint source, or referencing source. The designing process of this reference book will elucidate the cosmetic characteristics of Surabaya dance (Tari Surabaya) in which most of the society have less recognition about it. The character in the designing process of this reference book represents the cosmetic characteristics of Surabaya dance that. The cosmetic characteristic of Surabaya dance reference book projected to design the cosmetic characteristic of Surabaya dance reference book as an information medium for Surabaya society. In order to support the book, the research employs photography technique that believes could produce a clear, and high quality image. By the existence of the photography technique, the information about cosmetic characteristic of Surabaya dance could become informative and interesting. The informative and interesting book will amplify the reading interest.Kata Kunci: Buku Referensi, Karakteristik Tata Rias, Tari Surabaya